Efficient microbial synthesis of key steroidal intermediates from bio-renewable phytosterols by genetically modified Mycobacterium fortuitum strains. Issue 15 (8th July 2019) - Liu, Na; Feng, Jinhui; Zhang, Rui; Chen, Xi; Li, Xuemei; Yao, Peiyuan; Wu, Qiaqing; Ma, Yanhe; Zhu, Dunming
Abstract : Two genetically modified strains of Mycobacterium fortuitum ATCC 6841 were created and applied to the transformation of phytosterols into HIP and HIL in high yields with no detectable by-products. Abstract : 3aα- H -4α-(3′-Propionic acid)-5α-hydroxy-7aβ-methylhexahydro-1-indanone-δ-lactone (sitolactone, or HIL) and 3aα- H -4α-(3′-propionic acid)-7aβ-methylhexahydro-1, 5-indanedione (HIP) are important intermediates for the synthesis of a variety of steroidal medicines with an α-methyl group or without the methyl group at the C10-position. Although they can be prepared by chemical synthesis or microbial transformation of steroids, their low efficiency and the formation of by-products limit their application. In this study, by investigating the degradation pathway of steroidal C/D rings and analyzing the metabolites in the catabolism of phytosterols by the genetically modified strains Δ fadD3 and Δ fadE30 of Mycobacterium fortuitum (ATCC 6841), two carboxylic acid reductase genes ( car1 and car2 ) were identified to be involved in the degradation of HIP. The inactivation of these two car genes in strains Δ fadD3 or Δ fadE30 blocked the generation of other metabolites and enhanced the accumulation of HIP or HIL, respectively. At the preparative scale, the recombinant strains transformed phytosterols into HIP or HIL at 20 g L −1 substrate concentration in 88% or 75% yields, respectively, without detectable by-products. This offers an economically feasible and green process for the industrial production of these important intermediates from bio-renewable phytosterols, cheap and abundant by-products of the plant oil industry.